2019
DOI: 10.1029/2019jg005114
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Shifts Create Complex Transient Distributions of Particulate Organic Carbon and Biogeochemical Responses in Beach Aquifers

Abstract: Biogeochemical reactions within intertidal zones of coastal aquifers have been shown to alter the concentrations of terrestrial solutes prior to their discharge to surface waters. In organic‐poor sandy aquifers, the input of marine organic matter from infiltrating seawater supports active biogeochemical reactions within the sediments. However, while the seasonality of surface water organic carbon concentrations (primary production) and groundwater mixing have been documented, there is limited understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…Due to its reduced mobility, particulate organic matter is further trapped in intertidal sediments. This “carbon memory” has been observed to enhance microbial rates for up to 2 months (Kim et al, ). It is thus likely that both August and October rates have been affected by the high pelagic activity in prior months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its reduced mobility, particulate organic matter is further trapped in intertidal sediments. This “carbon memory” has been observed to enhance microbial rates for up to 2 months (Kim et al, ). It is thus likely that both August and October rates have been affected by the high pelagic activity in prior months.…”
Section: Discussionmentioning
confidence: 99%
“…Advective flow of seawater through sediments supplies benthic microbial communities with oxygen (O 2 ) and nitrate (NO 3 − ), as well as particulate and dissolved organic matter, thus leading to high rates of organic matter degradation and nutrient turnover (Anschutz et al, 2009;Huettel & Rusch, 2000b;Kim et al, 2019). As such, coastal permeable sediments can contribute substantially to marine organic carbon remineralization, thereby affecting coastal nutrient and metal budgets (Huettel et al, 1998;Huettel et al, 2014;Van Raaphorst et al, 1990).…”
Section: Ahrens Et Al 1 Of 21mentioning
confidence: 99%
“…In beach aquifers, such particulate transport dynamics and frequent shifts in hydrologic conditions result in a spatially variable distribution of POC across the beach aquifer ( Figure 1a). Recent field investigations at Cape Shores, Lewes, DE, USA, showed that these pools of reactive POC, potentially from algal fragments, beach wrack, and seagrass, retarded in their movement relative to groundwater flow, are important sources of nutrients and biogeochemical reactivity to the adjacent porewater (Kim et al, 2019). Numerical models also suggest that dissolution of POC from buried wrack can serve as an important organic carbon source to fuel reactivity in the beach (Heiss, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During wave and tide activity, seawater travels up the beachface and infiltrates into the aquifer, overtopping seaward flowing fresh groundwater (Abarca et al, 2013; Michael et al, 2005; Robinson et al, 2006). The mixing between fresh groundwater and saline seawater creates a saltwater circulation cell in the intertidal zone (Heiss & Michael, 2014; Michael et al, 2005; Robinson et al, 2006; Vandenbohede & Lebbe, 2006), which hosts dynamic biogeochemical reactions (Hays & Ullman, 2007; Kim et al, 2017, 2019; Slomp & Van Cappellen, 2004; Spiteri, Slomp, Tuncay, & Meile, 2008; Ullman et al, 2003). Fresh groundwater delivers terrestrial nutrients such as nitrate to the beach aquifer, which can be utilized as an alternative electron acceptor after oxygen depletion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation